(untitled) (Acta Scientiarum. Health Sciences, 2012)
Neuropsychiatric complications are present in almost one third of patients diagnosed with AIDS who show wide variations in their clinical symptoms, featuring a spectrum of disorders ranging from minor cognitive-motor impairments to profound dementia. The Mini Mental State Examination (MMSE) is one of the most used and studied cognitive tests around the world and evaluates cognitive function and screening of dementia. Current experiment applies the MMSE to HIV/AIDS patients to screen possible dementia factors in the sample and to evaluate the association of scores that are positively associated with the emergence of cognitive impairment and possible dementia. The study population consisted of 100 HIV/AIDS patients attended at the 15 th and 17th Regional Health Centers covering 50 municipalities in the northwestern region of the state of Paraná, Brazil. Whereas patients were classified with cognitive impairment and patients without cognitive impairment, the factors assessed included depression, body mass index, haematocrit, hemoglobin levels, rate of lymphocytes T CD4+, viral load and gender. Twenty-seven (27%) patients had scores lower than expected and were considered cognitively impaired. There was a significant positive association between cognitive impairment and changes in blood hemoglobin and haematocrit, age and depression.